Анализ процессов в индукторной системе с притягивающим экраном, возбуждаемой внешним круговым соленоидом - Чаплыгин, Е.А. (Електротехніка і електромеханіка, 2015)
В статье представлен теоретический анализ пространственно-временных распределений индуцированных токов и
сил притяжения в «индукторной системе с притягивающим экраном», возбуждаемой плоским круговым соленоидом,
расположенным с внешней стороны вспомогательного экрана. Показана, достаточно высокая эффективность системы, что позволяет рекомендовать её как инструмент внешней рихтовки вмятин в кузовных покрытиях автотранспорта. У статті представлений теоретичний аналіз просторово-часових розподілів індукованих струмів і сил притягання в
«індукторній системі з притягуючим екраном», що збуджується плоским круговим соленоїдом, розташованим із зовнішнього боку допоміжного екрана. Показана, досить висока ефективність системи, що дозволяє рекомендувати її як
інструмент зовнішнього рихтування вм'ятин в кузовних покриттях автотранспорту. Introduction. Developments in the field of magnetic-pulse
treatment of metals (MPTM) are increasingly used in the modern technologies of production and repair of the aviation, automotive and other machinery, as they are environmentally
friendly and energy-efficient in comparison with classical approaches. One of the main components of the device MPTM is a
tool – inductor or the inductor system with an attractive screen
(ISAS). The calculated dependences to calculate the inductor
system with an attractive screen were taken from previous
works. The ratios were obtained for the low-frequency mode of
the excited fields, when is place their significant penetration
through a thin-walled metal screen and a deformed workpiece.
As it was shown earlier this mode is the most efficient from point
of view of a force action on the object of a processing. Purpose.
The theoretical analysis of the spatial-temporal distributions of
the induced currents and forces of an attraction in the inductor
system with an attractive screen excited by a flat circular solenoid located on the outside of the auxiliary screen. Methodology. The calculations are shown that the induced currents both
in the screen and the workpiece are unidirectional and their
interaction, in accordance with the law of Ampere determines
the amplitudes of excited forces of attraction. Let’s note the
effective validity of the considered inductor system excited by an
external circular solenoid. With sufficient simplicity of the design take place rather high values of the developed forces of
attraction and their averages. Results. Physically, a higher
power efficiency of the system with an «external» coil in comparison with a system where coil is located in the internal cavity, can be accounted for lade of «failure» in the radial distribution of the excited forces. This «failure» in the design with a coil
between the sheet metal is caused by its screening action against
the forces of attraction between the induced currents. Practical
value. It is shown that the inductor system with an attractive
screen when it is excited by outer circular solenoid with a current of 50 kA ~ provides attractive power rates to about 1400 N
on an area of sheet metal ~ 0.004 m2
. The sufficiently high efficiency of the proposed options of an inductor system allows us
to recommend it as a tool of the external straightening dents in
the bodycar surfaces of vehicles.